“The Concept of Punitive Damages: Balancing Criminal Legislation and Judicial Practice” - Omer Al-Khalid, Assist. Prof. Aseel (Basra studies journal, 2025)
This study examines the concept of punitive damages in the context of balancing criminal legislation and judicial practice. The research is divided into two sections. The first section addresses the concept of punitive damages, its definition, objectives, and characteristics, as well as its subjectivity by explaining its elements and legal nature. The second section is devoted to clarifying the acts that warrant a ruling for punitive damages and examining similar applications within Iraqi legislation. The study reaches several conclusions and recommendations. Principally, punitive damages are not alien to legal thought in Arab countries with a Latin-based system, such as Iraq and Tunisia, even though Iraqi law does not explicitly use the term “punitive damages,” which is reflected in the similar applications observed in practice. The key recommendation is that the Iraqi legislator should adopt a clearer, more detailed, and illustrative approach, formally integrating the concept of punitive damages alongside the penalties prescribed for criminal acts under the Penal Code.